Teamwork makes the dream work: Testing for shared perceptions on psycho-behavioural skills between athletes, coaches and parents - Laureys, F.; Deconinck, F. J.; Lenoir, M.; Collins, D. (Psychology of Sport and Exercise, 2023)
Psycho-behavioural skills play a key role in optimising progression through talent development, and this study investigated to what extent athlete`s self-perceptions align with those of their coaches and parents. Firstly, we examined if levels of alignment between these three raters differ across age of the athlete. To this end, 122 athletes between 9 and 18 years old (12.17 ± 2.41 years old; 47 gymnasts, 13 cyclists and 62 badminton players) completed a psycho-behavioural questionnaire. The ANOVA`s indicated low levels of correspondence between the ratings of the athlete, the coach and the parents during childhood, while better levels of shared perceptions were found in adolescence. Secondly, we investigated to what extent coaches and parents believed their own perception of the athlete`s and the perception of the athlete`s psycho-behavioural skills were accurate. Parents appeared to be more confident in accurately perceiving the psycho-behavioural skills of the athlete than coaches. Parents and coaches also believed that older athletes would be more honest on their psycho-behavioural shortcomings than younger athletes. Altogether, these findings highlight that athletes and other stakeholders in the talent development environment should strive for better alignment in perceptions on psycho-behavioural skills during the talent development pathway. With better integrated perceptions, a more functional and efficient talent development system for the athlete targeting the psycho-behavioural skills can be created.